Pengaruh Earning Per Share (EPS), Price To Book Value (PBV), dan Return On Assets (ROA) Terhadap Harga Saham pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia Periode 2021 -2024 - Roidatun Nada; Deasy Tantriana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study is aimed at examining the extent of the influence of earnings per share (EPS), price to book value (PBV), and return on assets (ROA) on stock price movements in companies listed in the lq45 index on the Indonesia Stock Exchange (IDX) in 2021 to 2024. The approach used is a quantitative approach with associative properties, namely looking at the relationship between variables, where data analysis will be carried out using secondary data taken from the company's annual financial statements on the Indonesia Stock Exchange (IDX) and stock closing price data published on public platforms such as yahoo finance. Purposive sampling technique used in sorting research samples, while to analyze the data used multiple linear regression method with the help of SPSS application. The results of this study showed that partially, EPS, PBV, and ROA variables each have a positive and significant influence on stock prices. When tested simultaneously, these three variables also showed a significant effect with the magnitude of the coefficient of determination (R2) reached 0.668. This shows that 66.8% of the stock price changes can be explained by these three variables, while the remaining 33.2% are influenced by other factors that are not included in the research model. These results prove that the company's financial performance, especially reflected in the ability to generate profits and market views, has an important contribution in determining the share price in the Indonesian capital market.